2007
DOI: 10.1007/s00428-006-0364-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical and post-mortem findings in intensive care unit patients

Abstract: The autopsy has long been regarded as an important tool for clinical confrontation, education and quality assurance. The aims of this study were to examine the correlation between the clinical diagnosis and autopsy findings in adult patients who died in an intensive care unit (ICU) and to identify the types of errors in diagnosis to improve quality of care. Autopsies from 289 patients who died in the ICU during a 2-year period were studied. Post-mortem examination revealed unexpected findings in 61 patients (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 47 publications
4
40
2
4
Order By: Relevance
“…In present study Male-to-female ratio was 1:1.47, while in other MICU studies like Maris C et al [6] and Aline Fusco et al [7] male-to-female ratio was 1.5:1 and 1.72:1 respectively, which is discordant with our study. Female preponderance in our study can be explained by the fact that there were deaths in MICU due to pregnancy related complications.…”
Section: Discussioncontrasting
confidence: 54%
“…In present study Male-to-female ratio was 1:1.47, while in other MICU studies like Maris C et al [6] and Aline Fusco et al [7] male-to-female ratio was 1.5:1 and 1.72:1 respectively, which is discordant with our study. Female preponderance in our study can be explained by the fact that there were deaths in MICU due to pregnancy related complications.…”
Section: Discussioncontrasting
confidence: 54%
“…7,25,28 This was not confirmed by our study (33.3% of discrepant cases). The difference may result from the limitation of our group to hematological patients and previously reported decreasing incidence of misdiagnosed pulmonary embolism.…”
contrasting
confidence: 55%
“…This finding is in accordance with various studies. 5,7,16,25,26 However, the number of undiagnosed infections in some studies is higher. 18,27 A more detailed analysis showed that 42.1% of the Aspergillus spp.…”
mentioning
confidence: 96%
“…Infectious diseases compromise the majority of missed causes of death in the various autopsy studies (2,4,5,13,15,17,18,20,21,30,31), especially when reporting cases from the ICU setting. Thus, the recognition of the source of infection remains a crucial unresolved problem and reinforces the difficulty of diagnosing different infectious entities such as peritonitis, pneumonia, endocarditis, and fungal infections in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%